Human resources management and ethics : responsibilities, actions, issues, and experiences - Sims, Ronald R.; Bias, Sheri K. (Contemporary human resource management., 2020)
"Human Resources Management and Ethics: Responsibilities, Actions, Issues, and Experiences, explores and provides an in-depth look at the responsibilities, actions, issues and experiences related to HRM and ethics for individual employees, organizations and the broader society. Like other departments in the broader organization HRM professionals will need to increasingly demonstrate how they contribute to an organization's ethical orientation and overall performance or success. While the ethical challenges, trends, and issues impacting employees, organizations and HRM professionals will continue to change over the years (consider the recent ethical challenges related cybersecurity and data breaches) the bottom-line of organization success is the clear reality that doing the right thing or institutionalizing an ethical culture or character is just as important to various stakeholders. The chapters in this book provide an updated, current and future look at the relationship between HRM and ethics and across various sectors or organizations (i.e. public, private, not-for-profit, academic, etc.). That is, this book discusses the ever evolving role of HRM professionals to include discussion of how the profession continues to take on more responsibility for developing and institutionalizing an ethical culture in their organizations, industries and the broader society. The book also contributes to the need for ongoing dialogue, discussion or insights offered by HRM experts on what HRM professionals and their organizations can do in the face of ethical expectations, challenges and scandals. In the end, the book is intended to increase our understanding of the ethical responsibilities, actions, issues and experiences that arise both within HRM and in HRM's interactions with individuals and organizations"--